2011
DOI: 10.1007/s12272-011-0801-0
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the chemical composition and possible mechanisms underlying the antispasmodic and bronchodilatory activities of the essential oil of Artemisia maritima L.

Abstract: This study describes the chemical composition of the essential oil of Artemisia maritima (Am.Oil) and the pharmacological basis for its medicinal use in gut and airways disorders. Twenty five compounds, composing 93.7% of the oil, were identified; among these, chrysanthenyl propionate and elixene were identified for the first time from any Artemisia species. The Am.Oil (0.3-1.0 mg/mL) suppressed spontaneous and high K(+) (80 mM)-induced contractions in isolated rabbit jejunum, suggestive of an antispasmodic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 59 publications
3
16
0
Order By: Relevance
“…Recent studies have confirmed antimicrobial (Krist et al, 2008;Pattnaick et al, 1997) antifungal (Pattnaick et al, 1997), antimalarial (Su et al, 2008), insecticidal (Prates et al, 1998), anthelmintic (Shah et al, 2011), antiexudant, cytotoxic, antitumor (Asanova et al, 2003, antispasmodic (Magalhaes et al, 1998), antiinflammatory (Santos & Rao, 2000), analgesic (Asanova et al, 2003;2000), and gastroprotectant (Santos & Rao, 2001) properties of 1,8-cineole. It has been reported that 1,8-cineole alters neural firing in certain areas of the olfactory lobe.…”
Section: Introductionmentioning
confidence: 91%
“…Recent studies have confirmed antimicrobial (Krist et al, 2008;Pattnaick et al, 1997) antifungal (Pattnaick et al, 1997), antimalarial (Su et al, 2008), insecticidal (Prates et al, 1998), anthelmintic (Shah et al, 2011), antiexudant, cytotoxic, antitumor (Asanova et al, 2003, antispasmodic (Magalhaes et al, 1998), antiinflammatory (Santos & Rao, 2000), analgesic (Asanova et al, 2003;2000), and gastroprotectant (Santos & Rao, 2001) properties of 1,8-cineole. It has been reported that 1,8-cineole alters neural firing in certain areas of the olfactory lobe.…”
Section: Introductionmentioning
confidence: 91%
“…It was suggested that essential oils, either inhaled or applied on the skin, act through their lipophilic fractions on the lipid moieties of cell membranes and, therefore, modify the activity of calcium and potassium ion channels . Applied to a certain dose, essential oils saturate the membranes.…”
Section: Mechanism Of Action Of the Bioactive Components Of Essentialmentioning
confidence: 99%
“…It was suggested that essential oils, either inhaled or applied on the skin, act through their lipophilic fractions on the lipid moieties of cell membranes and, therefore, modify the activity of calcium and potassium ion channels. [27][28][29][30] Applied to a certain dose, essential oils saturate the membranes. They seem to interact with cell membranes depending on the structure and physicochemical properties of the components that can then affect the function of various membrane molecular structures [31] : transport systems, enzymes, ion channels [32,33] or receptors.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Interestingly, all plants tested were found to contain Ca ++ channel blocking (CCB)‐like constituents, which co‐existed with either PDE inhibitory and/or antimuscarinic constituents. Some popular herbs commonly used in asthma and cough, such as turmeric ( Curcuma longa ), St. John's wort ( Hypericum perforatum ), Artemisia maritima , Andropogon muricatus and Juniper excelsa , were found to possess bronchodilatory effect, mediated through a combination of CCB and PDE inhibitory activities (Gilani et al , , ; Shah et al , ; Shah and Gilani, ; Khan et al , ). Similarly, the essential oil of Nepeta cataria also mediates airways relaxation, through a combination of same dual inhibitory mechanisms (Gilani et al , ).…”
Section: Discussionmentioning
confidence: 99%